Two-dimensional shear wave elastography and ultrasound-guided attenuation parameter for progressive non-alcoholic steatohepatitis. - Hidekatsu Kuroda; Yudai Fujiwara; Tamami Abe; Tomoaki Nagasawa; Takuma Oguri; Sachiyo Noguchi; Naohisa Kamiyama; Yasuhiro Takikawa (PLoS ONE)
Background and aims We investigated the usefulness of combining two-dimensional shear wave elastography and the ultrasound-guided attenuation parameter for assessing the risk of progressive non-alcoholic steatohepatitis, defined as non-alcoholic steatohepatitis with a non-alcoholic fatty liver disease activity score of ≥4 and a fibrosis stage of ≥2. Methods This prospective study included 202 patients with non-alcoholic fatty liver disease who underwent two-dimensional shear wave elastography, ultrasound-guided attenuation parameter, vibration-controlled transient elastography, the controlled attenuation parameter, and liver biopsy on the same day. Patients were grouped according to liver stiffness measurement using two-dimensional shear wave elastography and the attenuation coefficient, assessed using the ultrasound-guided attenuation parameter: A, low liver stiffness measurement/low attenuation coefficient; B, low liver stiffness measurement/high attenuation coefficient; C, high liver stiffness measurement/low attenuation coefficient; and D, high liver stiffness measurement/high attenuation coefficient. Results Two-dimensional shear wave elastography and vibration-controlled transient elastography had equivalent diagnostic performance for fibrosis. The areas under the curve of the ultrasound-guided attenuation parameter for identifying steatosis grades ≥S1, ≥S2, and S3 were 0.89, 0.91, and 0.92, respectively, which were significantly better than those of the controlled attenuation parameter (P<0.05). The percentages of progressive non-alcoholic steatohepatitis in Groups A, B, C, and D were 0.0%, 7.7%, 35.7%, and 50.0%, respectively (P<0.001). The prediction model was established as logit (p) = 0.5414 × liver stiffness measurement (kPa) + 7.791 × attenuation coefficient (dB/cm/MHz)-8.401, with area under the receiver operating characteristic curve, sensitivity, and specificity values of 0.832, 80.9%, and 74.6%, respectively; there was no significant difference from the FibroScan-aspartate aminotransferase score. Conclusion Combined assessment by two-dimensional shear wave elastography and the ultrasound-guided attenuation parameter is useful for risk stratification of progressive non-alcoholic steatohepatitis and may be convenient for evaluating the necessity of specialist referral and liver biopsy.